Analisis Kualitas Pelayanan Prima Menggunakan Dimensi Service Quality (Servqual) di Feast Restaurant Sheraton Bandung Hotel and Towers: - Erwin Setiawan; Rizki Subagja; Dadi Indra Permana (Akademi Pariwisata NHI Bandung, 2025)
Excellent service plays a crucial role in achieving customer satisfaction in the hospitality and restaurant industry. This study aims to analyze the quality of service at Feast Restaurant, Sheraton Bandung Hotel and Towers. The research employs a descriptive method with a qualitative approach, using data collection techniques such as observation, interviews, questionnaires, and literature studies. The findings indicate that while most customers experience convenience in the service, several aspects require improvement, namely speed, empathy, accuracy, and reliability. To address these issues, enhancing service quality through employee training and better management practices is necessary. These findings highlight the importance of employee development to achieve excellent service standards that meet customer expectations and enhance the restaurant's competitiveness in the hospitality industry.